Memories of Vladimir Mikhailovich Galushin (1932–2024) - Anatoly F. Kovshar (Пернатые хищники и их охрана)
Vladimir Mikhailovich Galushin had a radiant personality: with great talent and equally great contribution to science, the education of ornithological staff, environmental education, and the protection of birds of prey, he always remained simple, attentive, and tolerant (his favourite word) to his colleagues. Therefore, many of us will miss his involvement in our endeavours for a long time. His works will be in demand for many years, and the memory of this wonderful man and comrade will remain in our hearts as long as we can remember something…